Revealing the role of metformin in gastric intestinal metaplasia treatment - Hu, Ruoyu; Xue, Xia; Sun, Xiangdong; Mi, Yang; Wen, Huijuan; Xi, Huayuan; Li, Fuhao; Zheng, Pengyuan; Liu, Simeng (Frontiers in Pharmacology, 2024)
Gastric intestinal metaplasia (IM) is a precancerous stage associated with gastric cancer. Despite the observed beneficial effects of metformin on IM, its molecular mechanism remains not fully elucidated. This study aims to reveal the effects and potential mechanisms of metformin in treating IM based on both bioinformatics and in vivo investigations.The seven public databases (GeneCards, DisGeNET, OMIM, SuperPred, Pharm Mapper, Swiss Target Prediction, TargetNet) were used in this work to identify targeted genes related to IM and metformin. The shared targeted genes between metformin and IM were further analyzed by network pharmacology, while the interactions in-between were investigated by molecular docking. In parallel, the therapeutic effect of metformin was evaluated in IM mice model, while the core targets and pathways effected by metformin were verified in vivo.We screened out 1,751 IM-related genes and 318 metformin-targeted genes, 99 common genes identified in between were visualized by constructing the protein-protein interaction (PPI) network. The top ten core targeted genes were EGFR, MMP9, HIF1A, HSP90AA1, SIRT1, IL2, MAPK8, STAT1, PIK3CA, and ICAM1. The functional enrichment analysis confirmed that carcinogenesis and HIF-1 signaling pathways were primarily involved in the metformin treatment of IM. Based on molecular docking and dynamics, we found metformin affected the function of its targets by inhibiting receptor binding. Furthermore, metformin administration reduced the progression of IM lesions in Atp4a -/-mice model significantly. Notably, metformin enhanced the expression level of MUC5AC, while inhibited the expression level of CDX2. Our results also showed that metformin modulated the expression of core targets in vivo by reducing the activity of NF-κB and the PI3K/AKT/mTOR/HIF-1α signaling pathway.This study confirms that metformin improves the efficacy of IM treatment by regulating a complex molecular network. Metformin plays a functional role in inhibiting inflammation/apoptosis-related pathways of further IM progression.Our work provides a molecular foundation for understanding metformin and other guanidine medicines in IM treatment.